Vibration isolation using a hybrid lever-type isolation system with an X-shape supporting structure - Liu, Chunchuan; Jing, Xingjian; Li, Fengming (International journal of mechanical sciences, 2015)
This study presents some novel results about analysis and design of low-frequency or broadband-frequency vibration isolation using a hybrid lever-type isolation system with an X-shape supporting structure in passive or semi-active control manners. It is shown that the system has inherent nonlinear stiffness and damping properties due to structure geometrical nonlinearity. Theoretical analysis reveals that the hybrid isolation system can achieve very good ultra-low-frequency isolation through a significantly-improved anti-resonance frequency band (by designing structure parameters). Noticeably, the system can realize a uniformly-low broadband vibration transmissibility, which has never been reported before. Cases studies show that the system can work very well with good isolation performance subject to multi-tone and random excitations. The results provide a new innovative approach to passive or semi-active vibration control (e.g., via a simple linear stiffness control) for many engineering problems with better ultra-low/broadband-frequency vibration suppression. •A hybrid isolation system is proposed to achieve excellent ultra-low-frequency isolation.•An anti-resonance frequency region can be much improved.•The system can also achieve uniformly low vibration transmissibility over full frequency.•Excellent isolation performance can be designed flexibly with structure parameters.